KAZAKHSTAN’S NATIONAL COMPETITIVENESS - SABDEN, Orazaly; DODONOV, Vyacheslav (CENTRAL ASIA AND THE CAUCASUS, 2007)
The problem of assessing Kazakhstan’s national competitiveness has been actively discussed since March 2006. The rankings used to assess national (country) competitiveness are calculated by the World Economic Forum (WEF) in the form of a special index coupled with a separate Business Competitiveness Index (BCI). Prior to 2006, national competitiveness was assessed in terms of the Growth Competitiveness Index (Growth CI), which has now been replaced by a Global Competitiveness Index (GCI). Based on 2005 results, Kazakhstan was 61st in the Growth CI among 117 countries, trailing behind India’s 50th place by 0.27 points (with a score of 3.77 against 4.04). In terms of the component indexes of the Growth CI, Kazakhstan’s positions were as follows: rank 77 in the technology index, rank 41 in the macroeconomic environment index, and rank 76 in the public institutions index. For comparison: Russia’s rankings in these component indexes were 73, 58 and 91, respectively (with an overall Growth CI rank of 75). Changes in the indexes assessing national competitiveness had an effect on the methodology used to calculate these indicators. This change in methodology, for its part, led to a change in the positions of individual countries. Thus, Kazakhstan now occupies 56th place in the GCI rankings. Nevertheless, this is not progress but regress compared to 2005, because under the new methodology the republic ranked 51st and not 61st, as in the Growth CI rankings. The same applies to various component indexes, including the macroeconomy, in which the country now ranks 10th, so that some commentators talk about an unprecedented breakthrough from 41st place in 2005. But it is incorrect to compare these places in the rankings, because the WEF now evaluates the macroeconomic successes of countries using other methods. There have been changes both in formulas and indicators and in the name of the given index. Today it is simply called “macroeconomy,” whereas a year earlier the term was “macroeconomic environment index.” In assessing macroeconomic competitiveness, the WEF now takes into account only six statistical indicators (hard data), whereas in the past its calculations were based on 10 indicators, including survey data. Consequently, Kazakhstan’s current 10th place in 2006 cannot be compared with its 41st place in 2005, because these rankings were compiled based on totally different indexes.